Effect of an electronic nicotine delivery device (e cigarette) on desire to smoke and withdrawal, user preferences and nicotine delivery: randomised cross-over trial. Issue 2 (8th April 2010) - Bullen, C; McRobbie, H; Thornley, S; Glover, M; Lin, R; Laugesen, M
Abstract : Objectives: To measure the short-term effects of an electronic nicotine delivery device ("e cigarette", ENDD) on desire to smoke, withdrawal symptoms, acceptability, pharmacokinetic properties and adverse effects. Design: Single blind randomised repeated measures cross-over trial of the Ruyan V8 ENDD. Setting: University research centre in Auckland, New Zealand. Participants: 40 adult dependent smokers of 10 or more cigarettes per day. Interventions: Participants were randomised to use ENDDs containing 16 mg nicotine or 0 mg capsules, Nicorette nicotine inhalator or their usual cigarette on each of four study days 3 days apart, with overnight smoking abstinence before use of each product. Main outcome measures: The primary outcome was change in desire to smoke, measured as "area under the curve" on an 11-point visual analogue scale before and at intervals over 1 h of use. Secondary outcomes included withdrawal symptoms, acceptability and adverse events. In nine participants, serum nicotine levels were also measured. Results: Over 60 min, participants using 16 mg ENDD recorded 0.82 units less desire to smoke than the placebo ENDD (p=0.006). No difference in desire to smoke was found between 16 mg ENDD and inhalator. ENDDs were more pleasant to use than inhalator (p=0.016) and produced less irritation of mouth and throat (p<0.001). On average, the ENDD increased serum nicotine to a peak of 1.3 mg/ml in 19.6 min, the inhalator to 2.1 ng/ml in 32 min and cigarettes to 13.4 ng/ml in 14.3 min. Conclusions: The 16 mg Ruyan V8 ENDD alleviated desire to smoke after overnight abstinence, was well tolerated and had a pharmacokinetic profile more like the Nicorette inhalator than a tobacco cigarette. Evaluation of the ENDD for longer-term safety, potential for long-term use and efficacy as a cessation aid is needed. Trial registration: No.12607000587404, Australia and New Zealand Clinical Trials Register